2021
DOI: 10.1038/s41598-021-90184-9
|View full text |Cite
|
Sign up to set email alerts
|

Folliculin haploinsufficiency causes cellular dysfunction of pleural mesothelial cells

Abstract: Birt–Hogg–Dubé syndrome (BHDS), an autosomal dominant inheritance disease caused by folliculin (FLCN) mutations, is associated with lung cysts and spontaneous pneumothorax. The possibility of FLCN haploinsufficiency in pleural mesothelial cells (PMCs) contributing to development of pneumothorax has not yet been clarified. Electron microscopy revealed exposed intercellular boundaries between PMCs on visceral pleura and decreased electron density around the adherens junctions in BHDS. To characterize cellular fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…adhesion junction protein VE-cadherin, ZO-1 a linker protein and β-catenin one of components of cell–cell adhesion machinery [ 32 36 ]. We demonstrated that HPMC successfully form tight and adhesion junctions which is in concordance with previously published works using HPMC monolayer as a model to assess the functional integrity of the peritoneum [ 37 ] and pathogenesis of pneumothorax [ 38 ] underlying the importance of our established in vitro system. We assessed the permeability of our system and detected decrease in permeability of 3D organotypic co-culture model of pleura compared to collagen matrix with fibroblasts and polymer mesh without cells up to age of 3 days after complete construction of 3D co-culture model.…”
Section: Discussionsupporting
confidence: 89%
“…adhesion junction protein VE-cadherin, ZO-1 a linker protein and β-catenin one of components of cell–cell adhesion machinery [ 32 36 ]. We demonstrated that HPMC successfully form tight and adhesion junctions which is in concordance with previously published works using HPMC monolayer as a model to assess the functional integrity of the peritoneum [ 37 ] and pathogenesis of pneumothorax [ 38 ] underlying the importance of our established in vitro system. We assessed the permeability of our system and detected decrease in permeability of 3D organotypic co-culture model of pleura compared to collagen matrix with fibroblasts and polymer mesh without cells up to age of 3 days after complete construction of 3D co-culture model.…”
Section: Discussionsupporting
confidence: 89%
“…Haploinsufficiency at FLCN has also been reported in BHDS manifestations 10,11 . FLCN protein is similar to DENN domain proteins, though its exact function is unknown 12 .…”
Section: Introductionmentioning
confidence: 90%
“…BHDS renal tumours exhibit loss of heterozygosity (LOH), suggesting a tumour suppression role of FLCN in kidney 9 . Haploinsufficiency at FLCN has also been reported in BHDS manifestations 10,11 . FLCN protein is similar to DENN domain proteins, though its exact function is unknown 12 .…”
Section: Introductionmentioning
confidence: 90%
“…FLCN encodes a protein known as folliculin [ 4 ], which is believed to act as a tumor suppressor, based on Knudson’s two-hit hypothesis, in BHDS-associated renal tumors [ 5 , 6 ]. However, unlike renal tumors, no somatic variants or loss of heterozygosity has been detected in either skin [ 7 ] or pulmonary lesions, suggesting that haploinsufficiency can induce the phenotypes observed in these tissues [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%